Wound coverage considerations for leg defects: Our experience - Bharat Mishra; Shivam Dang; Pallab Chatterjee; Pranay Pratap (Journal of Marine Medical Society, 2024)
Background: Lower limb injuries are common and account for 40-50% of emergency department visits. These injuries occur frequently in poly-trauma, which remains a leading cause of long hospitalization, disability and death for all ages. Clinical treatment of these injuries poses a great challenge because the surgeons need to face serious complications such as shock, wound coverage and infection, and has to choose a right time to deal with the combined fractures and injuries of the blood vessels, nerves and tendons. The aim of this study is to study clinical profile and management of various below knee soft tissue injuries. Methods: This study was conducted in two tertiary care centres of Northern India. Subjects were recruited from patients presenting in Emergency/Surgery OPD, a primary diagnosis of lower limb soft tissue injuries. Results: A total of 125 patients with lower limb injuries were included in the study. Different treatment options were individualized and exercised which included skin grafting (49.6%), flap coverage (44%) primary closure (4.8%) and skin substitutes like Integra (1.6%). While in 46 wounds (36.8%) negative pressure wound therapy (NPWT) VAC was used. It was observed that 92 patients (73.6%) underwent surgery only once whereas 33(26.4%) patients had to undergo surgery 2 or more times. Conclusion: The aim of surgical treatment in lower limb reconstructions is maximum limb functional recovery and return to work activities. Problems in reconstruction are mainly encountered in the ankle and lower third leg defects because, local tissue availability is very minimal in these areas.